The effect of managerial ownership, institutional ownership, and market activity on firm value - Silalahi, Beatrice Mora Ulidya; Lestari, Tri Utami (Gema Wiralodra, 2023)
This study aims to determine the effect of managerial ownership, institutional ownership, and market activity on firm value. The research method used in this research is causal quantitative. The population in this study are property & real estate sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique used in this study was a purposive sampling technique, and a total of 49 company samples were obtained. The data analysis method used in this research is using panel data regression analysis method. The research data was obtained from the website www.idx.co.id. The results of the partial test show that managerial ownership and institutional ownership do not affect firm value. Meanwhile, market activity has a negative effect on firm value. Keywords: Managerial Ownership, Institutional Ownership, Market Activity, Firm Value